THE LIFE OF GERVAISE MACQUART AS A LOWER WORKING CLASS WOMEN UNDER FRENCH SECOND EMPIRE IN THE NOVEL L’ASSOMMOIR BY ÉMILE ZOLA - Teguh Basuki; Arifah Arum Candra H. (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The industrialization which developed in the 19th century France had brought both positive and negative impacts. Some of the negative impacts are the rising number of labors, the emergence of inter class conflicts, social problems such as prostitution, and the oppression of lower class women. This research will discuss about the life of lower class women depicted in the novel L’Assommoir by Émile Zola, as the portrayal of the reality in the French Second Empire. The analysis uses qualitative descriptive technique and applies Foucaults’s theory on social exclusion, Beauvoir’s theory of second sex, and also gender theory. The analysis shown that Zola criticize the inequalities in the life of lower class women under Second Empire. It also shows that lower class women excluded from the ‘grand’ discourse in French society. The exclusion process which is done by society and supported by the State at that time regarded as a normal thing and ‘taken for granted’.